Communication and Measurement of the University Social Responsibility: Social Networks and Indicator Proposal - Aldeanueva Fernández, Ignacio (2018)
This research analyzes the behavior of 50 variables related to corporate social responsibility in the area of communication of every Spanish university. To this aim, more than 25,0000 twits sent by the Twitter accounts of said universities—both private and public—were analyzed. Several different algorithms were applied to measure the frequency of concepts linked to the semantic universe of corporate social responsibility. The results reveal an unequal presence of these terms in the universities’ outgoing messages and an alarmingly reduced median, which leads us to conclude that these concepts are not part of these institutions’ outgoing communication. Based on this, future lines of research, as well as a unique system of university social responsibility indicators are proposed.